Only Near Is Dear? Doing Elderly Care with Everyday ICTs in Indian Transnational Families - Tanja Ahlin (MEDICAL ANTHROPOLOGY QUARTERLY, 2017)
In Kerala, South India, young people, especially women, are encouraged to become nurses in order to migrate abroad for work and thereby improve the financial status of their family. Meanwhile, many of their parents remain in India by themselves. This is occurring in the context of a strong popular discourse of elder abandonment, related to the local norms of intergenerational co-habitation. Based on fieldwork in Kerala and one of the nurses’ destination countries, Oman, I present evidence that complicates this discourse by showing how: (1) migration is a form of elder care practice in itself; and (2) care for the elderly continues across countries and continents with the help of information and communication technologies (ICTs). Using the theoretical approaches of science and technology studies, I analyze ICTs as key members of care collectives and argue that ICTs have a significant role in reshaping care relations at a distance. [care, aging, ICTs, migration, Indian transnational families]